2018
DOI: 10.1093/jrr/rry083
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the radioprotective effects of thymoquinone on dynamic thiol-disulphide homeostasis during total-body irradiation in rats

Abstract: Ionizing radiation–induced free radicals cause functional and structural harmful effects. Thiol, an important antioxidant, plays a major role in the eradication of reactive oxygen molecules. Thiol/disulphide homeostasis is a marker of oxidative stress. The objective of this study was to assess the potential radioprotective effects of thymoquinone (TQ) on the dynamic thiol/disulphide homeostasis of rats receiving total-body irradiation (IR). Twenty-two rats were divided into three groups to test the radioprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…TQ had antioxidant activity and reduced oxidative stress induced by IR, as shown by the complex thiol/ disulfide homeostasis, according to Deniz et al, (2019) study. As a result, using TQ prior to radiation therapy protected the rats from oxidant side effects.…”
Section: Discussionmentioning
confidence: 81%
“…TQ had antioxidant activity and reduced oxidative stress induced by IR, as shown by the complex thiol/ disulfide homeostasis, according to Deniz et al, (2019) study. As a result, using TQ prior to radiation therapy protected the rats from oxidant side effects.…”
Section: Discussionmentioning
confidence: 81%
“…A study was conducted to examine the potential effects of TQ to check on the balancing effect of sulfides homeostasis of irradiated rats and to evaluate its radioprotective effectiveness. TQ treatment showed that disulfide and native thiol to that of total thiol ratio to be significantly different (p=0.003) from the sham and irradiated groups [36].…”
Section: Thymoquinone (Tq)mentioning
confidence: 82%
“…IR provides treatment for various indications in cancer; however, it has also harmful effects caused by the formation of free radicals. Presence of any agent that can reduce toxicity of IR on normal cells would be very valuable in decreasing the side effects [ 21 ]. This study investigated the radioprotective effects of melatonin and TQ on the damage induced by radiation when the rats received total-body IR at a single-dose.…”
Section: Discussionmentioning
confidence: 99%